2020
DOI: 10.1111/apt.16193
|View full text |Cite
|
Sign up to set email alerts
|

Drug survival of anti‐TNF agents compared with vedolizumab as a second‐line biological treatment in inflammatory bowel disease: results from nationwide Swedish registers

Abstract: SummaryBackgroundComparisons of second‐line anti‐tumour necrosis factor (TNF) agents and vedolizumab are sparse.AimTo evaluate the effectiveness of anti‐TNF agents compared to vedolizumab as second‐line biologics in inflammatory bowel disease (IBD).MethodsA propensity score‐matched cohort was created using Swedish nationwide registers. Patients with Crohn's disease or ulcerative colitis, exposed to first‐line anti‐TNF treatment, who initiated a second anti‐TNF agent or vedolizumab in 2014‐2016 (N = 1363) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 45 publications
(56 reference statements)
0
6
0
Order By: Relevance
“…Studies using DS as an efficacy endpoint are fewer in number. A nationwide Swedish register-based study assessing DS for second-line treatment with IFX and VDZ showed similar DS between these medications [ 13 ]. Based on a claims database, a second study from the USA described drug persistence (sustainability) tendencies, with slightly longer drug persistence for IFX, without direct comparison between the drugs and no adjustment to different factors that might affect DS [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies using DS as an efficacy endpoint are fewer in number. A nationwide Swedish register-based study assessing DS for second-line treatment with IFX and VDZ showed similar DS between these medications [ 13 ]. Based on a claims database, a second study from the USA described drug persistence (sustainability) tendencies, with slightly longer drug persistence for IFX, without direct comparison between the drugs and no adjustment to different factors that might affect DS [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…TNF inhibitors are Infliximab, Adalimumab, Golimumab and Certolizumab pegol. They antagonize TNF receptors and induce inhibition of immune responses by TNF, thus inducing recovery and maintenance of remission of CD and UC [ 55 ]. Generally, the most common manifestation of anti-TNF hepatotoxicity is acute hepatocellular damage, which occurs on average 13 weeks after the start of therapy.…”
Section: Biologic Therapiesmentioning
confidence: 99%
“…As the first biological agents, anti-tumor necrosis factor (anti-TNF) monoclonal antibodies, mainly including infliximab and adalimumab, have been widely used to treat moderate to severe IBD patients over the past two decades and have been proven effective and mature ( Derkx et al, 1993 ; D'Haens and van Deventer, 2021 ; Rundquist et al, 2021 ). Unfortunately, 10%–40% of patients fail to respond favorably to the anti-TNF therapies for the first time, which is called primary non-response (PNR) ( Ben-Horin et al, 2014 ; Papamichael et al, 2015 ; Sabino et al, 2019 ; Marsal et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%